Formation Of Value Orientations in Older Preschoolers on The Basis of Karakalpak Folk Traditions - E.S.Jaksimuratova; Sh.B.Saparov (Zien Journals, 2021)
The spiritual "reproduction" of the nation is ensured by the fact that children are brought up on the cultural and historical values of their grandfathers and great-grandfathers." Personality formation takes place in the process of assimilation of a multifaceted social experience in the form of a system of ideas about the world, about morality and a system of behavioral stereotypes fixed by traditions. In the social experience of each nation there are elements of universal and national values.
Keywords: elements; grandfathers; ensured; Personality